British Association of Dermatologists guidelines for the management of people with rosacea 2021. (5th July 2021) - Hampton, P.J.; Berth‐Jones, J.; Duarte Williamson, C.E.; Hay, R.; Leslie, T.A.; Porter, I.; Rauz, S.; Seukeran, D.; Winn, R.T.; Hashme, M.; Exton, L.S.; Mohd Mustapa, M.F.; et al.
Abstract : Linked Comment:  J.S.S. Ho and Y. Asai. Br J Dermatol 2021; 185 :689–690 . Plain language summary available online